ANALISIS LEARNING OBSTACLE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI STATISTIKA DI SMP NEGERI 1 KUALA - Syuhaya, Nanda; Aklimawati; Hidayat, Amam Taufiq (Ar-Riyadhiyyat: Journal of Mathematics Education, 2025)
The learning obstacle experienced vary for students, which causes students to still have difficulty solving mathematical problems. Therefore, this study aims to determine the learning obstacles to student’s mathematical problem-solving abilities in statistics material at SMP Negeri 1 Kuala. The learning obstacle that will be discussed is the epistemological obstacle. The research method used is descriptive. Data collection techniques in this study are written tests, interviews and documentation. Data analysis was carried out by data correction, data reduction, data display, and conclusion drawing/verification. The research subjects consisted of 3 students of class VII-2 SMP Negeri 1 Kuala who were selected based on the results of the student’s mathematical problem-solving ability test answers based on high, medium and low categories represented by 1 student in each category. The results showed that students with high mathematical problem-solving abilities experienced procedural and operational technique epistemological obstacles. Furthermore, students with moderate mathematical problem-solving abilities experienced conceptual, procedural and operational technique epistemological obstacles. Meanwhile, students with low mathematical problem-solving abilities experienced procedural and operational technique epistemological obstacle.